A new strategy for enhancing the thermo-mechanical and chemical stability of dual-phase mixed ionic electronic conductor oxygen membranes. Issue 35 (17th August 2016) - Yun, Kyong Sik; Park, Jeong Hwan; Kwon, Young-il; Kim, Dong Young; Yoo, Chung-Yul; Yu, Ji Haeng; Joo, Jong Hoon
Abstract : A mixed ionic electronic conductor (MIEC) membrane with chemical and thermo-mechanical stability has been developed. Abstract : A mixed ionic electronic conductor (MIEC) membrane with thermo-mechanical and chemical stability has been developed. A fluorite-rich dual-phase composite (80 vol% Ce0.9 Gd0.1 O2− δ –20 vol% La0.7 Sr0.3 MnO3− δ ) based on the chemically stable pure electronic conductor oxide (LSM) and doped-ceria (GDC) was used as the membrane material. By introducing a thermo-mechanically and chemically stable coating material (Pr2 NiO4+ δ ) to the membranes, this study proposes a new strategy for enhancing the overall stability of the oxygen permeation ceramic membrane. The stability of the dual-phase membrane was assessed in the presence of CO2 at intermediate temperatures, and thermal cycling tests were performed to evaluate its performance under extreme conditions. The dual-phase membrane with Pr2 NiO4+ δ coating layer not only showed remarkable stability in a pure CO2 atmosphere but also exhibited thermo-mechanical stability during rapid thermal cycling tests (cooling and heating rate: 30 °C min −1 ).